2017
DOI: 10.31269/triplec.v15i2.867
|View full text |Cite
|
Sign up to set email alerts
|

Who is Actually Harmed by Predatory Publishers?

Abstract: 'Predatory publishing' refers to conditions under which gold open access academic publishers claim to conduct peer review and charge for their publishing services but do not, in fact, actually perform such reviews. Most prominently exposed in recent years by Jeffrey Beall, the phenomenon garners much media attention. In this article, we acknowledge that such practices are deceptive but then examine, across a variety of stakeholder groups, what the harm is from such actions to each group of actors. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Another important issue is the effects of predatory publishing on different stakeholders as for instance discussed by Eve and Priego [45] or Frandsen [32]. First there is the effect of the articles on the science of other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue is the effects of predatory publishing on different stakeholders as for instance discussed by Eve and Priego [45] or Frandsen [32]. First there is the effect of the articles on the science of other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Note that this definition was published after the article by This is a not peer-reviewed preprint to an article submitted to Science of the Total Environment Sonne et al (2020). In a recent paper, Eve and Priego (2017) queried who is actually harmed by "predatory publishers", and concluded that any harm is negligible to virtually all stakeholder groups, including researchers. However, they also noted that "established publishers have a strong motivation to hype claims of predation as damaging to the scholarly and scientific endeavour while noting that, in fact, systems of peer review are themselves already acknowledged as deeply flawed".…”
Section: (Ii) Open Access Predatory Journalsmentioning
confidence: 99%
“…Predatory journals may be something of a red herring, in terms of actual harm that they cause (Eve & Priego, 2017). Commentators have argued that the real predators may be the dominant big academic publishers (Olijhoek & Tennant, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%